2016
DOI: 10.1016/j.jmb.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Intrinsically Disordered C-Terminal Domain of SSB Reveals DNA-Mediated Compaction

Abstract: The bacterial single stranded DNA binding protein SSB is a strictly conserved and essential protein involved in diverse functions of DNA metabolism, including replication and repair. SSB comprises a wellcharacterised tetrameric core of N-terminal oligonucleotide binding (OB) folds that bind single-stranded DNA (ssDNA) and four intrinsically disordered C-terminal domains of unknown structure that interact with partner proteins. The generally accepted, albeit speculative, mechanistic model in the field postula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…The IDL is rich in Gly (17), Pro (9) and Gln plus Asn (14). As a result of this composition, the E. coli IDL is predicted to form an ensemble of compact globular conformations [27], consistent with hydrodynamic studies [27] and small angle x-ray and neutron scattering studies [56]. Such globular conformations may promote positive cooperativity through linker-linker interactions upon ssDNA binding.…”
Section: Discussionmentioning
confidence: 65%
“…The IDL is rich in Gly (17), Pro (9) and Gln plus Asn (14). As a result of this composition, the E. coli IDL is predicted to form an ensemble of compact globular conformations [27], consistent with hydrodynamic studies [27] and small angle x-ray and neutron scattering studies [56]. Such globular conformations may promote positive cooperativity through linker-linker interactions upon ssDNA binding.…”
Section: Discussionmentioning
confidence: 65%
“…This sequence composition likely contributes to the movements of the C-terminal domain of the protein associated with ssDNA binding. 45 Our analysis of the linker region of EcSSB suggests that the amino acids present in the region from Q117 to Q147 have a propensity to form a PPII-like helix. [46][47][48] This is supported by modeling which showed that this region could adopt a structure resembling a collagen monomer.…”
Section: Discussionmentioning
confidence: 79%
“…The presence of this collection of repeats confers elastomeric properties such as those observed in the eukaryotic proteins enabling the C‐terminal 69 residues to adopt different conformations thereby facilitating a larger range of partner proteins with which SSB can bind. This sequence composition likely contributes to the movements of the C‐terminal domain of the protein associated with ssDNA binding …”
Section: Discussionmentioning
confidence: 99%
“…While phosphorylation of the tyrosine 82 dramatically increased the SsbA affinity for single-stranded DNA (6), phosphorylation of the threonine 38 enhanced the capacity of SsbA tetramers to attach adjacently to a single-stranded DNA substrate. It was recently demonstrated that the disordered C-terminal region of bacterial Ssb proteins collapses towards the tetramer upon DNA-binding (20), thus leading to a more compact structure. It is tempting to speculate that phosphorylation of threonine 38 could lead to a specific interaction with the C-terminal domains of adjacent SsbA monomers, and thereby aid the compacting process upon binding single-stranded DNA.…”
Section: Electrophoretic Mobility Shift Assaymentioning
confidence: 99%